The Effectiveness of Strength Based Intervention Motivational interviewing Group Counseling to Improve Students’ Self Compassion (Universitas Negeri Semarang, 2019)
This study aimed to analyze the effectiveness of strength based intervention motivational interviewing group counseling to improve students’ self-compassion. The study used pretest and multiple posttest design. Purposive sampling was used to select 14 experimental subjects which were grouped into two in random or in other words, 7 people for each group. For more, the data collection technique in this study used self-compassion scale-short form (SCS-SF). The results of mixed repeated measures ANOVA showed that strength based intervention motivational interviewing group counseling was effective to improve self-compassion (F (1.12) = 365.97, p < 0.05). This also could be seen in the effect of time (F (2,24) = 424.98, p < 0.05), and interaction effect between time and group (F (2,24) = 581.59, p < 0.05). These findings assert that strength based intervention motivational interviewing group counseling is effective to improve students’ self-compassion.